2015
DOI: 10.1186/s12885-015-1914-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of proto-oncogene BRF2 in breast cancer cells by the dietary soybean isoflavone daidzein

Abstract: BackgroundBRF2 is a transcription factor required for synthesis of a small group of non-coding RNAs by RNA polymerase III. Overexpression of BRF2 can transform human mammary epithelial cells. In both breast and lung cancers, the BRF2 gene is amplified and overexpressed and may serve as an oncogenic driver. Furthermore, elevated BRF2 can be independently prognostic of unfavorable survival. Dietary soy isoflavones increase metastasis to lungs in a model of breast cancer and a recent study reported significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 63 publications
(66 reference statements)
0
28
1
Order By: Relevance
“…Daidzein belongs to the family of isoflavones, and is abundant in soybeans and soy-based products; and therefore, may be easily obtained from daily dietary intake (32)(33)(34). Known as a type of phytoestrogen, daidzein has been reported to serve an estrogen-like function in hormone-dependent cells, including prostate cells, breast cells, and Sertoli and Leydig cells of the testes (35)(36)(37). Daidzein exhibits anti-tumor activity, including a pro-apoptotic function in numerous tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Daidzein belongs to the family of isoflavones, and is abundant in soybeans and soy-based products; and therefore, may be easily obtained from daily dietary intake (32)(33)(34). Known as a type of phytoestrogen, daidzein has been reported to serve an estrogen-like function in hormone-dependent cells, including prostate cells, breast cells, and Sertoli and Leydig cells of the testes (35)(36)(37). Daidzein exhibits anti-tumor activity, including a pro-apoptotic function in numerous tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…This may allow silenced tumour suppressor genes to be re‐expressed, indicating a potential beneficial effect of genistein. However, inhibition of DNMT may also lead to a reduced methylation of proto‐oncogenes, as has been shown for coumestrol, daidzein and equol (Lyn‐Cook et al , ; Koo et al , ), which may indicate a possible adverse effect. However, whether these findings from in vitro studies are relevant for the in vivo situation remains to be established, since genistein has been shown to cause an increase in DNA methylation upon exposure in vivo , such as in the agouti mouse model as mentioned above (Dolinoy et al , ) and in humans (Qin et al , ).…”
Section: Introductionmentioning
confidence: 93%
“…However, another study reported that daidzein treatment (3–10 μM) up-regulated proto-oncogene BRF2 in ER-positive breast cancer cells but not ER-negative cells. Female mice treated with a high-isoflavone commercial diet showed significantly increased BRF2 expression [129]. …”
Section: Experimental Studiesmentioning
confidence: 99%